(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Encephalocele is defined as protrusion of cranial contents like meninges and cerebral tissue beyond the normal confines of the skull through a defect in the cranium. It is one form of a neural tube defect as are anencephaly and spina bifida. There are 2 main types of encephalomeningocele, frontoethmoidal and occipital, according to the location of the defect. The frontoethmoidal type defect, which is located in the area of the frontal and ethmoidal bones. The authors present a case of frontonasal encephalocele in a very young child. Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 58-62